Digital competence across boundaries-beyond a common Nordic model of the digitalisation of K-12 schools? - Olofsson Anders D.; Lindberg J. Ola; Pedersen Alex Young; Arstorp Ann-Thérèse; Dalsgaard Christian; Einum Even; Caviglia Francesco; Ilomäki Liisa; Veermans Marjaana; Häkkinen Päivi; Willermark Sara (TAYLOR & FRANCIS LTD, 2022)
This paper explores policy related to digital competence and the digitalisation of Nordic K-12 schools. Anchored in some key transnational policies on digital competence, it describes some current Nordic movements in the national policies of Denmark, Finland, Norway and Sweden. The concept of boundary objects is used as an analytical lens, for understanding digital competence as a plastic and temporal concept that can be used to discuss the multi-dimensional translation of this concept in these Nordic countries. The paper ends with a discussion of the potential to view digital competence as a unifying boundary object that, with its plasticity, temporality and n-dimensionality, can show signs of common Nordic efforts in the K-12 school policy.